Effect of Ca Ionophore On Blastocyst Production Following Intracytoplasmic Sperm Injection in Caprine Oocytes. (11th May 2016) - Kharche, SD; Pathak, J; Agarwal, S; Kushwah, B; Sikarwar, AKS
Contents: The aim of the present investigation was to study the effect of calcium ionophore activation on blastocyst production following intracytoplasmic sperm injection (ICSI) in in vitro ‐matured Caprine oocytes. A total of 470 in vitro ‐matured oocytes were selected and randomly divided in to three groups. Cumulus oocyte complexes (COCs) recovered by slicing the Caprine ovaries were matured in TCM199 supplemented with 10% foetal bovine serum (FBS) + 10% follicular fluid + FSH (5 μg/ml) + LH (10 μg/ml) + estradiol (1 μg/ml) + EGF (10 ng/ml) + BSA (3 mg/ml) for 27 h in humidified atmosphere at 38.5°C with 5% CO2 in CO2 incubator. After 27 h of culture, selected COCs (n = 470) were separated from cumulus cells by treating with 0.1% hyaluronidase enzyme and passing repeatedly through a fine pipette and randomly divided into three groups. In group 1, (n = 168) matured oocytes were injected with injection micropipette without sperm as control. In group 2, (n = 152) capacitated spermatozoa were injected into cytoplasm of in vitro ‐matured oocytes through injection micropipette. In group 3, (n = 150) capacitated spermatozoa were injected into cytoplasm of in vitro ‐matured oocytes through injection micropipette and then activated with 5 μm Ca ionophore for 5 min. The oocytes of all groups were then culture in RVCL media for embryo development. The cleavage rate was observed after 48–72 h of injection. The cleavage rate and blastocyst production in group 1, 2 and 3 were 0.00 and 0.00, 18.42 and 3.57 and 61.33% and 16.30%, respectively. The result indicated that mechanical activation failed to induce cleavage in in vitro ‐matured Caprine oocytes, whereas chemical activation of intracytoplasmic sperm‐injected in vitro ‐matured Caprine oocytes showed significantly higher cleavage rate and blastocyst production as compare to non‐activated oocytes.